Study of Human Microglia Phenotypes via an In Vivo Neuroimmune Organoid Model (Molecular Medicine Communications, 2023)
Microglia are specialized brain-resident macrophages that play crucial roles in brain development, homeostasis, and disease. However, until now, the ability to model interactions between the human brain environment and microglia has been severely limited. To overcome these limitations, Schafer and colleagues developed an in vivo xenotransplantation approach that allows us to study functionally mature human microglia (hMGs) that operate within a physiologically relevant, vascularized immunocompetent human brain organoid (iHBO) model. Developing an in vivo neuroimmune organoid model to study human microglia phenotypes would involve creating a three-dimensional structure that mimics the complexity of the human brain and immune system. Such a model could provide a valuable tool to investigate the behavior and function of microglia, the resident immune cells of the central nervous system, in a more physiologically relevant context. Data from Schafer and colleagues show that organoid-resident hMGs gain human-specific transcriptomic signatures that closely resemble their in vivo counterparts. In vivo two-photon imaging reveals that hMGs actively engage in surveilling the human brain environment, react to local injuries, and respond to systemic inflammatory cues. Finally, they demonstrate that the transplanted iHBOs developed here offer the unprecedented opportunity to study functional human microglia phenotypes in health and disease and provide experimental evidence for a brain-environment-induced immune response in a patient-specific model of autism with macrocephaly. Cell. 2023 May 11;186(10):2111-2126.e20.  doi: 10.1016/j.cell.2023.04.022.